The role of internal CSR in guiding the digitalisation of work - Lea Wolf; Ronny Ehlen; Mona Bardmann; Caroline Ruiner; Julia Lanzl; Manfred Schoch; Henner Gimpel (International Journal of Corporate Social Responsibility (JCSR), 2024)
In the context of the increased use of digital technologies at work and the various reported positive and negative outcomes for workers, this paper deals with the effects of internal corporate social responsibility (ICSR) and the digitalisation of work. The findings are based on a structured literature review identifying and synthesizing extant knowledge. A total of 57 papers are analysed regarding their contributions to the literature on digital transformation and ICSR. The results indicate that ICSR is partly implemented in a reactive way to mitigate negative effects of digitalisation at work, and partly in a proactive way to prevent them. The contributions relate (a) to the conceptualisation of digital work and its effects related to ICSR; (b) to the development of the concept of ICSR with a specific focus on digitalisation; and (c) to the derivation of a future research agenda. Finally, implications for research and practice are discussed to investigate further ICSR's essential role in the interrelation between digitalisation and sustainability at work.
Keywords: 650; Digitalisation; ICT use; Internal CSR; Sustainability; Systematic literature review; Work